1996
DOI: 10.1016/0895-7061(96)00152-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between hypertension and other cardiovascular risk factors in survival of hemodialyzed patients

Abstract: The interaction of hypertension with other cardiovascular risk factors, namely hypercholesterolemia, smoking, and past history of cardiovascular complications, was examined. One hundred and ninety-five hemodialysis patients were followed up for 54.2 +/- 2.3 months, among whom 66 died. In patients with cardiovascular complications, such as ischemic heart disease, cerebrovascular accident, or atherosclerotic obliteration of peripheral arteries, and in patients older than 70 years, blood pressure had no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Several factors may contribute to the development of cardiovascular events, including hypertension, anemia, hyperparathyroidism, glucose intolerance, electrolyte disturbances, acidosis and hyperlipidemia [11, 12]. LVH is present in >70% of patients with ESRD [13]and is an important factor for the development of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may contribute to the development of cardiovascular events, including hypertension, anemia, hyperparathyroidism, glucose intolerance, electrolyte disturbances, acidosis and hyperlipidemia [11, 12]. LVH is present in >70% of patients with ESRD [13]and is an important factor for the development of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…[98][99][100][101] It is important to understand the precise mechanisms underlying the increase in cardiovascular events as renal function deteriorates and the capacity to excrete sodium into the urine is impaired, even in mild degree. 13,17,102 As discussed above, the incidence of stroke is increased in both saltsensitive hypertension and CKD.…”
Section: Pathophysiology Of the Cardiorenal Connectionmentioning
confidence: 99%
“…Recent studies have reported that this is due to an increasing prevalence of cardiac complications in this population [16]. Sudden cardiac death is the most common form of death in dialysis patients, accounting for 20% to 30% of all deaths in this cohort [17].…”
Section: Discussionmentioning
confidence: 93%